A Fulminant Case of Haemophilus influenzae Serotype F Meningitis in an Immunocompetent 3-Year-Old Boy - Wolf, Luise; Lippmann, Norman; Petzold-Quinque, Stefanie; Siekmeyer, Manuela; Kieß, Wieland (Journal of Pediatric Infectious Diseases, 2019)
Of all encapsulated Haemophilus influenzae (Hi), serotype b (Hib) is considered as the potentially most virulent one for children. After vaccination was introduced in the 1990s, the incidence of this serotype has dropped dramatically. Other encapsulated forms such as Hi serotype a, c, d, e, f (Hia-Hif) are diagnosed rarely and mostly affect vulnerable patient groups. As serotyping is not performed routinely, the number of unreported cases is estimated to be even higher. Whereas several cases of Hif disease in children with favorable outcome were published, a 3-year-old boy diagnosed with this serotype died at our hospital despite initial antimicrobial therapy.
Keywords: Haemophilus influenzae serotype f; bacterial meningitis; child; fatal outcome